2017
DOI: 10.1590/1518-8345.1378.2856
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factor analysis of the Appraisal of Self-Care Agency Scale - Revised

Abstract: Objective:to analyze the factor structure of the Appraisal of Self-Care Agency Scale-Revised (ASAS-R), adapted for Brazil. Method:methodological study conducted with 150 individuals with diabetes mellitus cared for by the Family Health Strategy, most of whom are elderly with low educational levels. The test of the hypothesis concerning the confirmatory factor composition of the ASAS-R was performed using latent variables structural equations. Results:the model’s goodness-of-fit indexes were satisfactory (χ2 = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 12 publications
2
25
1
15
Order By: Relevance
“…The results indicated that the current model fitted the data well, Chi2/df value was 2.331 which is less than 3 (Hoe 2008), GFI value was 0.951 which is close to the acceptable value of fit, CFI value was 0.958 which is higher than 0.95, RMSEA value was 0.061 which is greater than 0.05 and less than 0.10 (Hooper et al 2008, Bhat et al 2018. Finally, AGFI value was 0.862 which is higher than 0.80 (Stacciarini and Pace 2017) 3. Data analysis and results…”
Section: Model Fitmentioning
confidence: 93%
“…The results indicated that the current model fitted the data well, Chi2/df value was 2.331 which is less than 3 (Hoe 2008), GFI value was 0.951 which is close to the acceptable value of fit, CFI value was 0.958 which is higher than 0.95, RMSEA value was 0.061 which is greater than 0.05 and less than 0.10 (Hooper et al 2008, Bhat et al 2018. Finally, AGFI value was 0.862 which is higher than 0.80 (Stacciarini and Pace 2017) 3. Data analysis and results…”
Section: Model Fitmentioning
confidence: 93%
“…From this version, it derived a validated scale for the Brazilian population, which excluded 14 items, remaining grounded in the theory in three factors. 22 The successive psychometric tests of this last version of the ASA, carried out in different cultures, 2,23,29 have achieved a good adjustment. However, its use has shown so far only in a population with some chronic condition and in the elderly.…”
Section: Discussionmentioning
confidence: 94%
“…Similar results have been coinciding with other studies, such as the one conducted on a population in Costa Rica, 20 which also presents low correlation in the items 6, 7, 8, 11 and 20; the one of Colombia, 17 and that they have even proposed new ASA scale versions, generating smaller and even more, multidimensional scales. 2,3,22,23,29 In this study, the construct-related validation through a confirmatory and exploratory factorial analysis was explored. The analysis of the first produced a factorial solution of five factors, where an unclear and complex dimensional structure was observed, as it was not possible to recognize items that were conceptually related.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Según lo anterior, esta metodología suele ser utilizada en las ciencias sociales, en la investigación de mercados y en otras industrias que abarcan conjuntos de datos con dimensiones considerables (Gogni y Muiños, 2016; Rojas-Torres, 2016; Valdés-Moreno, Rodríguez-Márquez, Cervantes-Navarrete, Camarena y Gortari, 2016). En tal contexto, una de las pruebas más usadas para la validación de este análisis es la de Káiser-Meyer-Olkin (KMO), una herramienta que mide su nivel de aceptación (Stacciarini y Pace, 2017). En tanto, el análisis clúster es un conjunto de técnicas multivariantes utilizadas para clasicar a un conjunto de individuos en grupos homogéneos (Patias, Bobsin, Gomes, Liszbinski y Damke, 2016).…”
Section: Tablaunclassified